3D spheroid models of paediatric SHH medulloblastoma mimic tumour biology, drug response and metastatic dissemination - Sophie J. Roper (Nature Portfolio, 2021)
Abstract Studying medulloblastoma, the most common malignant paediatric brain tumour, requires simple yet realistic in vitro models. In this study, we optimised a robust, reliable, three-dimensional (3D) culture method for medulloblastoma able to recapitulate the spatial conformation, cell–cell and cell–matrix interactions that exist in vivo and in patient tumours. We show that, when grown under the same stem cell enriching conditions, SHH subgroup medulloblastoma cell lines established tight, highly reproducible 3D spheroids that could be maintained for weeks in culture and formed pathophysiological oxygen gradients. 3D spheroid culture also increased resistance to standard-of-care chemotherapeutic drugs compared to 2D monolayer culture. We exemplify how this model can enhance in vitro therapeutic screening approaches through dual-inhibitor studies and continual monitoring of drug response. Next, we investigated the initial stages of metastatic dissemination using brain-specific hyaluronan hydrogel matrices. RNA sequencing revealed downregulation of cell cycle genes and upregulation of cell movement genes and key fibronectin interactions in migrating cells. Analyses of these upregulated genes in patients showed that their expression correlated with early relapse and overall poor prognosis. Our 3D spheroid model is a significant improvement over current in vitro techniques, providing the medulloblastoma research community with a well-characterised and functionally relevant culture method.